Iron metabolism mediates the relationship between Vitamin C and hepatic steatosis and fibrosis in NAFLD - Hu, Zhengyu; Li, Yan; Ma, Bingwei; Lei, Saifei; Wang, Xingchun (Frontiers in Nutrition, 2022)
Vitamin C (Vit C) and iron metabolism are closely related to metabolic disorders. However, the relation between iron storage protein ferritin and Vit C has not been elucidated. We aimed to investigate the crosstalk between Vit C and ferritin and its implications on NAFLD. Clinical information of 3614 subjects was obtained from the NHANES Public Data 2017-2018. FibroScan data, which estimates liver steatosis and fibrosis and Vit C, were selected to assess factors influencing NAFLD in this cross-sectional study. Ferritin and Vit C among different categories of liver steatosis and fibrosis were assessed by CAP and E value. Logistic regression and RCS models were used to analyze the correlations. In vitro study in hepG2 were conducted to validate the regulations. Ferritin increased while Vit C decreased with more severe hepatic steatosis and hepatic fibrosis (all P<0.001). Logistic regression models indicated that increased serum ferritin was a risk factor for NAFLD while increased Vit C was a protective factor for NAFLD and hepatic fibrosis after adjusting the continuous and categorical variables. Vit C was negatively associated with ferritin. Further mediation analysis identified that ferritin mediates the impact of Vit C on NAFLD (P<0.05) and cirrhosis (P<0.001). The experiments on cellular level suggested Vit C alleviated PA/OA induced steatosis and maintains iron homeostasis through inhibiting PA/OA induced upregulation of iron bound protein ferritin and labile iron pool (LIP) induction in hepG2 cells. In conclusion, Vit C was a protective factor, whereas ferritin was a risk factor for hepatic steatosis and fibrosis. Vit C alleviated NAFLD and maintained iron homeostasis via ferritin suppression and LIP induction.